Solving ethical dilemmas with children: Empowering classroom research - Parr, Michelann (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
This article identifies and discusses ethical dilemmas inherent when undertaking research with children or other vulnerable populations: power relations, risks and benefits, and informed consent and confidentiality (Maguire, 2005). Ethical dilemmas often arise when researchers attempt to merge the interests of their research and the interests of their child participants. Classroom ethnography is offered as one example of how research can be conducted with children in a way that minimizes these ethical dilemmas. A case study is described in order to exemplify specifically how children respond when fully valued as speaking personalities and co-investigators. Conducted over a period of eight months, the inquiry and its participants moved through five phases that included initiating, exploring, implementing, adopting, and reflecting. Results suggest that legitimate consent, minimized risk, maximized benefit, and shared power through ownership, choice, and social action are of paramount importance when researching with children or any other vulnerable population.